Chatbot Positive Design to Facilitate Referencing Skills and Improve Digital Well-Being - Zaky, Yara Ahmed Mohebeldin (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This article examines the effectiveness of a positive-design chatbot in a mobile learning environment on students’ referencing‏ skills and digital well-being in a research context. The sample consisted of 150 postgraduate students at King Faisal University Education College who were writing their master’s dissertations and facing challenges regarding the preparation‏ of American Psychological Association 7th (APA7) edition-style scientific references. this search used a quasi-experimental study involving an achievement pretest and posttest together with a digital well-being scale to gather data and adopted a positive-design for a chatbot to be used in a mobile learning environment. We developed a chatbot mobile app called Smart Assistant for Research Referencing according to the proposed model and assessed its effect on skill development and digital well-being. The results showed that posttest knowledge increased significantly, and levels of digital well-being also improved. This study provides a model to help postgraduate students and researchers who use the APA7 style to prepare references faster, more easily, and with high accuracy. Where the researches results indicated that there is a problem in students' lack of APA reference skills and their frequent feelings of failure, frustration, anxiety and lack of motivation, the results of this research may help bridge the gap. Instructional designers may benefit from the proposed positive design model when designing positive learning environments based on artificial intelligence (AI). artificial intelligence to improve digital well-being.